2003
DOI: 10.1007/s00296-003-0317-0
|View full text |Cite
|
Sign up to set email alerts
|

Paraneoplastic eosinophilic fasciitis: a case report

Abstract: A 60-year-old white woman with polycythemia rubra vera post splenectomy in November 2001 was found to have peripheral white blood cell counts increasing over 3 months. Cytogenetics revealed trisomy of chromosomes 8 and 9, and bone marrow biopsy showed hypercellular, fibrotic bone marrow consistent with myelofibrosis of polycythemia rubra vera. Two months later, the patient developed acute swelling and pain in her lower extremities. The clinical symptoms along with confirmatory histology supported the diagnosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 5 publications
1
6
0
Order By: Relevance
“…In our case, the eosinophilic fasciitis preceded the detected metastases by 15 months, was unresponsive to corticosteroid therapy and improved following chemotherapy for the cancer. This is consistent with a paraneoplastic phenomenon 3 . Eosinophilic fasciitis is sometimes categorized with fibrosing conditions or scleroderma‐like diseases having similar histopathological features under the term ‘fasciitis–panniculitis syndromes’ 4 .…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…In our case, the eosinophilic fasciitis preceded the detected metastases by 15 months, was unresponsive to corticosteroid therapy and improved following chemotherapy for the cancer. This is consistent with a paraneoplastic phenomenon 3 . Eosinophilic fasciitis is sometimes categorized with fibrosing conditions or scleroderma‐like diseases having similar histopathological features under the term ‘fasciitis–panniculitis syndromes’ 4 .…”
Section: Discussionsupporting
confidence: 56%
“…Drugs, vigorous exercise, Borrelia infection and malignancy 2 have been implicated in the pathogenesis of this condition; however, most cases are idiopathic. Immunosuppressive medications have been used to treat this condition: partial improvement with corticosteroids is often noted 3 . Cases associated with malignancy are often refractory to corticosteroids, but may respond to chemotherapy 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Extensive skin induration of eosinophilic fasciitis can lead to joint contractures and tendon retraction, which reflect the severity of fascia fibrosis. A previous study showed that 29 among 52 patients had flexion contractures, 1 however, severe cases like ours are rare. Our patient also developed generalized skin hardening of the trunk, and his activities of daily living were much impaired by the disturbance of the range of excursion.…”
mentioning
confidence: 85%
“…Dear Editor, Eosinophilic fasciitis is occasionally associated with hematological malignancies. 1 We herein describe a case with eosinophilic fasciitis, generalized morphea and vitiligo, which developed into multiple myeloma.…”
mentioning
confidence: 96%
“…The absence of Raynoud's syndrome and unresponsiveness to corticosteroid treatment distinguishes eosinofilic fasiitis from scleroderma. [31,32] …”
Section: Paraneoplastic Eosinophilic Fasciitismentioning
confidence: 99%